Exploring factors of international students’ satisfaction: a case of Islamic universities in Malaysia - Amzat, Ismail Hussein; Kassim, Noorafini; Yusuf, Byabazaire; Hamed, Alyahmadi; Juping, Qiao; Khofiati, Ani (Institute of Advanced Engineering and Science, 2024)
No qualms, international student mobility has become a source of income for countries around the world. International students become more mobile, contributing to the university’s growth and diversity. It has also created competition by making higher institutions around the world develop strategies to attract them. This study explores the factors that lead to satisfaction among international students and the item indicator. This study is quantitative in nature, using a survey to collect the data. The population consists of international students from Asia, Africa, Europe, and Latin America at the leading Islamic universities in Malaysia. A total of 211 international students participated in the study. Ruffola Noel Levitz’s student satisfaction inventory, 2017 was used as an instrument, and a measurement model from SEM was applied to analyze the data. From the measurement model results, student-centeredness was ranked as the leading factor influencing international student satisfaction; followed instructional effectiveness. The main prediction or leading factor to improve international student satisfaction is to ensure international students’ positive feelings of self-belonging in Islamic universities in Malaysia. Improving instruction and service are also suggested to meet international student expectations and satisfaction. However, there is a scarcity of research conducted or published about Islamic universities worldwide, making Islamic universities neglected and difficult to find literature about.